HUBUNGAN ANTARA PERSEPSI DENGAN SIKAP KELUARGA DALAM MENANGANI ANGGOTA KELUARGA YANG MENGALAMI SKIZOFRENIA DI RSJD ATMA HUSADA MAHAKAM SAMARINDA - Dwi Rahmah Fitriani (Universitas Muhammadiyah Kalimantan Timur, 2017)
Background: A bad perception of the community against schizophrenic, considered difficult disease healing and disgrace of family. The bad perception that arises in the family is an issues for the family. This is not only gives rise to negative consequences for schizophrenic, but also can affect to a negative perception of family which subsequently resulted attitude of rejection, denial, and isolation for a schizophrenic. Family's role indispensable in healing for a schizophrenic. Purpose: The aim of this research is to identifying the correlation of perception with family attitude toward family members who experience schizophrenia at Atma Husada Mahakam Regional Psychiatric Hospital Samarinda.Methode: This research used a descriptive correlation design with cross sectional approach. The population of this research were 317 respondents. With purposive sampling technique obtained 76 samples. The data was collected through questionnaires and was analyzed with Pearson Product Moment.Results: The results of Pearson Correlation test showed correlation coefficient value of 0,858 with very strong correlation strength and significance level 0.000 (a <0,05).Conclusion : There is a significant correlation between of perception with family attitude towards family members who experience schizophrenia at Atma Husada Mahakam Regional Psychiatric Hospital Samarinda. Suggestions: For families of schizophrenia patient they are suggested to have a positively perception about schizophrenia that will be affect to positive attitude toward family members with schizophrenia to prevented the risk of schizophrenia recurrence.